Causal relationships exist between polycystic ovary syndrome and adverse pregnancy and perinatal outcomes: a Mendelian randomization study - Ma, Yuanlin; Cai, Jiahao; Liu, Lok-Wan; Wen, Tianrui; Huang, Weina; Hou, Wenhui; Wei, Zixin; Xu, Yan; Xu, Yanwen; Wang, Yizi; Mai, Qingyun (Frontiers in Endocrinology, 2024)
Introduction: Previous observational studies have shown that polycystic ovary syndrome (PCOS) was associated with adverse pregnancy and perinatal outcomes. However, it remains controversial whether PCOS is an essential risk factor for these adverse pregnancy and perinatal outcomes. We aimed to use instrumental variables in a two-sample Mendelian randomization (MR) study to determine causality between PCOS and adverse pregnancy and perinatal outcomes. Materials and Methods: We extracted summary statistics from a recent genome-wide association study (GWAS) meta-analysis conducted in PCOS, which included 10,074 cases and 103,164 controls of European ancestry. Adverse pregnancy and perinatal outcomes were summarised from the FinnGen database of European ancestry, which included more than 180,000 samples. The inverse variance weighted (IVW) method of MR was applied for the main outcome. To detect heterogeneity and pleiotropy, sensitivity analyses, including leave-one-out analysis, weighted median and MR-pleiotropy residual sum and outlier (MR-PRESSO), and MR-Egger regression were conducted. Results: Two-sample MR analysis with the IVW method suggested that PCOS exerted causal effects on the risk of hypertensive disorders of pregnancy (odds ratio [OR] 1.170, 95% confidence interval [CI] 1.051-1.302, P=0.004), in particular gestational hypertension (OR 1.083, 95%CI 1.007-1.164, P=0.031), but not other pregnancy and perinatal diseases (all P > 0.05). Sensitivity analyses demonstrated pleiotropy only in pre-eclampsia or eclampsia (P = 0.0004), but not other pregnancy and perinatal diseases (all P > 0.05). The results were consistent after excluding two outliers (all P > 0.05). Conclusions: We confirmed a causal relationship between PCOS and hypertensive disorders of pregnancy, in particular gestational hypertension, but no association with any other adverse pregnancy or perinatal outcome. Therefore, we suggest that women with PCOS who are pregnant should have their blood pressure closely monitored.